KAJIAN INTERTEKSTUAL DAN NILAI PENDIDIKAN NOVEL SANG PEMIMPI KARYA ANDREA HIRATA DAN NOVEL RANAH 3 WARNA KARYA AHMAD FUADI - tri indrayanti (Universitas PGRI Adi Buana Surabaya, 2014)
The research is purposed to explain and reveal (1) constituent structure of novel Sang Pemintpi and novel Ranah 3 Warna (2) The similarities and differences constituent structure of novel Sang Pemimpi and novel Ranah 3 Warna using intertextual approach (3) education value be contained of both of them. The research uses qualitative descriptive the methode used to find information sources and data in literature text, so that data are displayed in concepts or categories that are disable to account statistically. The collecting data technique that-is used: interactive technique contains of role observation and focus group discussion. Noninteractive technique contains of document writing and literature technique. In collecting data, the researcher releases that her position and her main role the collecting data tool (human instrument), so that the data kwality that are found dependend an the reseacher kwality. The data collection was analysed by analysis technique model interactive analysis with three steps of activity. (1) data reduction, (2) presenting data, and (3) conclusion or verification. The research finding of the researches, vised intertextual approach showing that the both of the novels (I) having constituent element that is unity, from the constituent eIernen that was found of novel Sang Pemimpi which published previously, it is hypograin. Whereas Ranah 3 Warna which publised finally called as the transformation. (2) constituent elements the both of the novels have similarities and differences. Those are: theme of the both of them is similar, it is the strunggling to face live and bellying of the dreams power, goal or hope: plot of the both of them has similarities, it is mixing plot (bundle of progressive plot and flasback plot); characthers and characteristics of the novels contain of protagonise character, antagonise character, main character and additional character; setting of the novels has different of setting place, primary setting of the novel Sang Pemimpi is in Manggar-Mangai, Bangka Belitong while novel Ranah 3 Warna is in IvIaninjau-Sumatra Barat, Bandung, and Canada; The point of view has differences, the novel Sang Pemimpi uses first point of view